Effects of beta-cypermethrin and myclobutanil on some enzymes and changes of biomarkers between internal tissues and saliva in reptiles (Eremias argus). (February 2019) - Chen, Li; Diao, Jinling; Zhang, Wenjun; Zhang, Luyao; Wang, Zikang; Li, Yao; Deng, Yue; Zhou, Zhiqiang
Abstract: Numerous studies suggested that reptiles are sensitive to environmental pollution and the abundance of many species are in decline. Our research is aim to assess the toxic effects of pesticide in reptiles. And we also want to supply some data about nondestructive samples for environmental risk assessment in reptiles. Lizards were orally administered a single-dose of beta-cypermethrin (BCP) or myclobutanil (MC) at the concentration of 20 mg/kg body weight (bw). The results showed that pesticides could induce changes in enzymatic activities (SOD, CAT, LDH, AChE) and MDA levels in organs or tissues of lizards. BCP could cause more severe oxidative damage than that of MC. Salivary enzymes activities showed sensitivity changes to the toxicity of pesticides. We could use saliva to reflect whether the reptiles are toxic by pesticides. We also agree that buccal swabs could be used as a tool for saliva sampling. Graphical abstract: Highlights: Beta-cyperimethrin can cause more oxidative severe damage than myclobutanil. Enzymes showed different changes in different organs or tissues. Salivary enzymes activities showed sensitivity changes in reptiles. Buccal swabs could be used as a tool for saliva sampling in reptiles.